Comportamiento agronómico del cultivo de acelga (Beta vulgaris l) con diferentes abonos orgánicos, en el colegio Pueblo Nuevo-El Empalme año 2014 - Carrera Vera, Holger Manuel (2015)
This research was conducted at the Agricultural Technical College "Pueblo Nuevo", belonging to the parish The Guayas, Canton El Empalme, is located between the geographical coordinates of 01 ° 06' south latitude and 79 ° 29 west longitude at an altitude of 73 meters. Working time was 120 days. To develop a design randomized complete (DBCA), with seven treatments and four replications was established. To determine the average resorted to the use of multiple range test Tukey 95% probability. Two types of fertilizer treatments were taken at different doses, where the treatment that best plant height was obtained T6 Dunger 5 kg was applied, with values of 48.38 cm at 45 days, plus get a significant of 2103.75 kg, positively influencing the production of spinach, according to statistical analysis T2 treatment including Humus 3 kg, was the treatment that presented the highest number of leaves at harvest with an average of 5.92 leaves, there are no statistical differences with the other treatments. The treatment I provide better results in the benefit / cost was the T2 (Humus 3 kg) and that for every dollar invested a profit of $ 0.50 was observed.